Using alternative therapies : a qualitative analysis - Low, Jacqueline, 1964- (Canadian Scholar's Press, 2004)
"This book provides a distinctive sociological inquiry into the perspectives and social issues surrounding the use of alternative therapies. Dr. Low presents the experiences of twenty-one Canadians who use alternative approaches to health care. Her study foregrounds the lay perspective by using a symbolic interactionist approach, emphasizing individuals' own understanding of reality as a basis for their actions." "Dr. Low analyses how and why the participants in the study came to use alternative therapies, and the ideologies informing the models of health and healing they espouse. She also discusses the impact these beliefs have on the participants, and the implications of their experiences for Canadian health care policy."--Jacket